Technoconsen(t)sus - Andrea M. Matwyshyn (Washington University Law Review, 2007)
This Article proposes to ease doctrinal noise in consent through creating an objective “reasonable digital consumer” standard based on empirical testing of real consumers. In a manner similar to the way in which courts assess actual consumer confusion in trademark law, digital user agreements can be tested for legal usability. Specifically, a particular digital agreement would be deemed to withstand an unconscionability challenge only to the extent that a drafter can demonstrate a “reasonable digital consumer” is capable of meaningfully understanding its terms and presentation. Part I of this Article introduces the challenges computer code presents to consent in the intellectual property space using the example of security-invasive DRM. It briefly describes DRM as a common business strategy for preemptively enforcing intellectual property rights. It then explains the negative consequences of this strategy for the information security of businesses, governments, and consumers. One of these negative consequences is industry confusion regarding the ethical norms of acceptable technology business conduct. Part II examines legal code and consent, placing the norm confusion described in Part I in legal context. This section describes the strain that the emergence of security-invasive DRM has placed on copyright law, computer intrusion law, and contract law in the United States. This tension forces us to come to terms with the preexisting problems of contractual consent and form contracts in a digital context. Current doctrinal construction of digital consent has analyzed user agreements only on grounds related to procedural unconscionability. This approach is flawed as a matter of contract doctrine: procedural and substantive unconscionability must be analyzed simultaneously under either Williston’s or Corbin’s standard of unconscionability. Either of these two approaches would correctly assess as unconscionable many current user agreements. Finally, Part III discusses the organizational code emerging at the intersection of computer code and legal code in digital contracting. It posits one possible legal approach to reconstructing meaningful consent in digital contracts in order to solve the problems of unconscionability discussed in Part II—generating an empirical objective “reasonable digital consumer” standard by looking to trademark law. Trademark case law offers well-established methods for determining whether a “reasonable” consumer is confused by a particular trademark or practice; these cases employ empirical testing by experts using real consumers. Importing this “legal usability testing” into digital contracting would benefit both users and content owners through creating predictability of legal outcome. Similarly, a reasonable digital consumer standard leverages the naturally occurring “hubs” of understanding that both courts and content owners seek to generate through form contracts. The proposed method strikes a successful balance between customization and standardization by using the real understandings of users. It also allows for evolution of these understandings over time as users’ familiarity with technology, and technology itself, advances.
Keywords: Consent (Law); Reasonable person standard (Law); Consumer protection; Computers & amp; privacy; Digital rights management